Pitfalls in Writing an Introduction for Research Manuscript Preparation for Publication - Suwisith, Nongluck (Thai Red Cross Nursing Journal, 2024)
Issues related to the preparation of manuscripts for research publication are well-addressed elsewhere. The introduction of the research report is the first part, allowing authors to present their problem of interest along with a set of existing knowledge and gaps identified, as well as the purpose of the study. An introduction of the report can capture the attention of both readers and reviewers, and provide an overview of the entire report. However, less attention has been given to the writing of introduction sections, resulting in common pitfalls in this initial part. This article aims to provide an essential guide for writing an introduction in research manuscript preparation. It addresses common problems and offers suggestions on how to revise these pitfalls, supported by examples. The content of this paper is expected to be helpful and support authors in producing effective manuscript preparations for their research reports for publication.